Semen cassiae Extract Inhibits Contraction of Airway Smooth Muscle - She, Yu-Shan; Ma, Li-Qun; Liu, Bei-Bei; Zhang, Wen-Jing; Qiu, Jun-Ying; Chen, Yuan-Yuan; Li, Meng-Yue; Xue, Lu; Luo, Xi; Wang, Qian; Xu, Hao; Zang, Dun-An; et al. (Frontiers in Pharmacology, 2018)
β2-adrenoceptor agonists are commonly used as bronchodilators to treat obstructive lung diseases such as asthma and chronic obstructive pulmonary disease (COPD); however, they induce severe side effects. Therefore, developing new bronchodilators is essential. Herbal plants were extracted and the extracts’ effect on airway smooth muscle (ASM) precontraction was assessed. The ethyl alcohol extract of semen cassiae (EESC) was extracted from Semen cassia. The effects of EESC on the Ach- and 80 mM K+-induced sustained precontraction in mouse and human ASM were evaluated. Ca2+ permeant ion channel currents and intracellular Ca2+ concentration were measured. HPLC analysis was employed to determine which compound was responsible for the EESC-induced relaxation. The EESC reversibly inhibited the Ach- and 80 mM K+-induced precontraction. The sustained precontraction depends on Ca2+ influx, and it was mediated by voltage-dependent L-type Ca2+ channels (LVDCCs), store-operated channels (SOCs), TRPC3/STIM/Orai channels. These channels were inhibited by aurantio-obtusin, one component of EESC. In addition, aurantio-obtusin inhibited the precontraction of mouse and human ASM and intracellular Ca2+ increases. These results indicate that Semen cassia extract inhibits sustained precontraction of ASM via inhibiting Ca2+-permeant ion channels, thereby, which could be used to develop new bronchodilators.